A novel terpolymer nanocomposite (carboxymethyl β-cyclodextrin–nano chitosan–glutaraldehyde) for the potential removal of a textile dye acid red 37 from water - Elbadawy, Hemmat A.; El-Dissouky, Ali; Hussein, Seham M.; El-Kewaey, Sara R.; Elfeky, Souad A.; El-Ghannam, Gamal (Frontiers in Chemistry, 2023)
Carboxymethyl β-cyclodextrin–nanochitosan–glutaraldehyde (CM-βCD:nChi:Glu ) terpolymer was successfully prepared as a nano-adsorbent for removal of anionic textile dye, acid red 37. The terpolymer nanocomposite formation and characterization were clarified by FTIR, XRD, SEM, TEM, BET specific surface area (BET-SSA) and zeta potential. The removal of the textile dye was investigated by batch adsorption method, investigating the effect of pH, dye concentration, adsorbent dose, contact time, and temperature. Results revealed that the maximum removal efficiency of 102.2 mg/L the dye is about 99.67%, under pH 6.0, the optimal contact time is 5 minutes, and the adsorbent dosage is 0.5g/L. At 29°C, adsorption capacity increased from 81.29 to 332.60 mg/g when the initial concentration of dye increased from 40.97 to 212.20 mg/L. Adsorption kinetics fitted well with the pseudo-second-order model with a good correlation (R² = 0.9998). The adsorption isotherm model can be best described by the Langmuir isotherm model. Based on the experimental results, the CM-βCD:nChi:Glu terpolymer has a promising potential as an efficient novel adsorbent for the removal of acid red 37 textile dye from contaminated water. The preparation techniques and demonstrated mechanisms in this study offer useful insights into the adsorbent-adsorbate interactions mechanism, analysis, challenges, and future directions of beta-cyclodextrin/chitosan-based adsorbents in wastewater treatment.